2019
DOI: 10.1111/dme.14103
|View full text |Cite
|
Sign up to set email alerts
|

Distinct trajectories of HbA1c in newly diagnosed Type 2 diabetes from the DPV registry using a longitudinal group‐based modelling approach

Abstract: Aim To identify groups of heterogeneous HbA1c trajectories over time in newly diagnosed Type 2 diabetes. Methods The study comprised 6355 adults with newly diagnosed Type 2 diabetes (55% men, median age 62 years, baseline BMI 31 kg/m2) from the Diabetes Patienten Verlaufsdokumentation (DPV) prospective multicentre diabetes registry (Germany, Austria). Individuals were assessed during the first 5 years after diabetes diagnosis if they had ≥ 3 aggregated HbA1c measurements during follow‐up. Latent class growth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
5
17
0
Order By: Relevance
“…This proportion of people attaining good glycaemic control was much lower than that in previous studies of patients with newly diagnosed type 2 diabetes and indicated the difficulty of long-term glycaemic control. [3][4][5] Higher HbA 1c measurements at one year were associated with higher baseline HbA 1c , higher body weight and low treatment adherence. 16 Long diabetes duration was a risk factor for poor glycaemic control and increased the difficulty of reaching the HbA 1c target.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This proportion of people attaining good glycaemic control was much lower than that in previous studies of patients with newly diagnosed type 2 diabetes and indicated the difficulty of long-term glycaemic control. [3][4][5] Higher HbA 1c measurements at one year were associated with higher baseline HbA 1c , higher body weight and low treatment adherence. 16 Long diabetes duration was a risk factor for poor glycaemic control and increased the difficulty of reaching the HbA 1c target.…”
Section: Discussionmentioning
confidence: 99%
“…Patients would benefit from early good glycaemic control and be inclined to develop long-term stable, good HbA 1c trajectory thereafter. [3][4][5][6][7] Severe hyperglycaemia could be decreased to the level of good glycaemic control within one year and then kept stable for the subsequent four years. 4 In this present analysis, the change of the percentage of subjects having a HbA 1c ≥7.50% decreased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations